Further notes on the flower chafer genus Platysodes Westwood, 1873 (Coleoptera: Scarabaeidae: Cetoniinae) with description of a new species from Himalaya - Qiu, Jian-Yue; Xu, Hao (Zootaxa, 2020)
Platysodes sabatinellii Qiu & Xu, new species, is described from southern Himalaya. Additional distributional records are given for the known species, and P. formosanus Kobayashi, 1990, which is previously considered endemic to Taiwan Island, is here recorded from the nearby Asian continent. An updated key to species of the genus is also presented.